2017
DOI: 10.1007/s10856-017-5885-8
|View full text |Cite
|
Sign up to set email alerts
|

In vivo osseointegration of dental implants with an antimicrobial peptide coating

Abstract: This study aimed to evaluate the in vivo osseointegration of implants with hydrophobic antimicrobial GL13K-peptide coating in rabbit femoral condyles by micro-CT and histological analysis. Six male Japanese Rabbits (4 months old and weighing 2.5 kg each) were included in this study. Twelve implants (3.75 mm wide, 7 mm long) were randomly distributed in two groups, with six implants in the experimental group coated with GL13K peptide and six implants in the control group without surface coating. Each implant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…39 We have previously demonstrated that homogeneous and robust peptide coatings can also been obtained on titanium Grade IV, other titanium alloys and zirconium oxide using the same silanization route than the one reported here. 40, 41…”
Section: Discussionmentioning
confidence: 99%
“…39 We have previously demonstrated that homogeneous and robust peptide coatings can also been obtained on titanium Grade IV, other titanium alloys and zirconium oxide using the same silanization route than the one reported here. 40, 41…”
Section: Discussionmentioning
confidence: 99%
“…Titanium surfaces modified with these chimeric peptides were found to significantly reduce adhesion of different Streptococcus species, S. aureus, S. epidermidis, P. aeruginosa , and E. coli , compared to bare titanium. Immobilization of GL13K onto titanium dental implants even enabled osseointegration when tested in rabbit femurs (Chen et al, 2017 ). Another promising strategy is the development of multifunctional coatings by combining the well-known RGD cell adhesive sequence with the lactoferrin-derived AMP LF1-11, resulting in in vitro cell integration as well as inhibition of bacterial colonization by S. aureus and Streptococcus sanguinis (Hoyos-Nogués et al, 2017 ).…”
Section: Preventive Strategiesmentioning
confidence: 99%
“…Keeping healing time in mind, placing an implant in a freshly extracted socket has gained popularity, with literature presenting clear guidelines for patient selection and methods of good outcomes (Zarandi & Novin, 2017;Schiegnitz et al, 2017;Chuka et al, 2017). Stability plays an important role in Osseointegration and primary stability directly influences the osseointegration of implants (Chen et al, 2017;Kim et al, 2017;Dhaliwal et al, 2017). A pre requisite for direct bone formation on the implant surface is achieved by initial implant stability on placement.…”
Section: Introductionmentioning
confidence: 99%